(3cJGH GdCOhjI GdeaQOI aj GdfHGJs - (3CMeO Hf eMeO Hf Hf CMeO Hf SjO GdZGabj, CHh LYaQs
(3ChdgG (B:s
(3bO cfJ TQYJ ai hVY cJGH ai GdCOhjI GdeaQOI GJNPJg JPcQI dfaSi hefYfi ef Pdc eG QCjJg ef bdI Cgd GdHUQ deG jhVY Ydi UhGH s
(3BNQgG (B:s
(3hjSei MH GdRde hgh GdeYQha YfOfG Hadad GdShOGf jRQY YfOfG RQYkG hCcKQ fHGJg HHdGO GdShOGf hgh HQi YfOge s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(242 / 6 (3b(B) s
Keywords: (3GdWHs